Lipoma in Superficial and Deep Lobes of Parotid Gland: A Case Report: - Soltani Gerdfaramarzi, Hamidreza; Moghimi, Mansour; Teimoori, Soraya (Galen Medical Journal, 2013)
Introduction: Lipomas among the most common benign neoplasms and rarely observed in parotid glands. We present a new case of lipoma in the superficial and deep lobes of the right parotid gland. Case report: A 52-year-old woman with painless and progressive inflation in the right preauricular region was referred to us. Computed Tomography scanning showed a hypodense area 5.2×4 cm in dimension in the right parotid gland region, and the facial nerve was fully exposed. The patient underwent parotidectomy, during which extensive removal of the mass was done. The pathology report cited a yellow-colored fatty tissue mass, 5×4×2 in dimension. In the microscopic report, lipoma of the parotid gland was seen.Conclusion: Determination of the exact tumor location is very important in the surgical approach in such cases. To our knowledge, this case seems to be an extremely rare case of lipoma in the superficial and deep lobes of the parotid. [GMJ. 2012;1(2):88-90]